Within All This Can Happen: Artefact, Hypermediacy, and W. G. Sebald - J Simpson (The International Journal of Screendance, 2016)
All This Can Happen, by David Hinton and Siobhan Davies, is a film based on a novella by Robert Walser, a writer who owned little, possessed no books, and invariably wrote on second-hand paper. The film’s integration of similarly borrowed materials and the nature of interactions between image, text, and sound are the central focus in this article which draws upon the work of W.G. Sebald and the vibrant field of related study as a means of analysis and enquiry. It specifically explores All This Can Happen’s embrace of archival conditions and decay, the interaction between fictive and authentic layers, and how complex hypermediated visual structures are facilitated by both the text’s grounding effect and its thematic focus on the act of walking.
Keywords: postdigital; aesthetics; archive; artefact; screendance; Sebald; Bolter and Grusin; hypermediacy; Walser; Barthes; photo-filmic; audio-visual; sound design; Chion; voiceover; decay; Cascone